Family Support Obligations From A Hadith Perspective - Henderi Kusmidi (NUSANTARA: Journal Of Law Studies, 2023)
This research aims to comprehensively discuss the issue of family support obligations from the perspective of the hadith of the Prophet Muhammad. This research is library research. The data collection technique used is documentation. The documentation technique was chosen because this study examines hadiths of the Prophet found in several hadith books. The analysis technique used is descriptive qualitative. An important finding in this research is that living is an obligation that must be carried out by the husband as head of the household. Fulfilling the obligation to provide support to the family is considered alms. Thus, if a husband works sincerely to meet the needs of his family, then the husband is like giving alms. The husband's obligation to provide for his wife's needs according to Islamic law is to fulfill household needs in terms of clothing, food and shelter according to the husband's capabilities. Islam does not provide definite standards regarding the limits and amount of maintenance that is the husband's obligation.